Investigating the Soliton-like Structures in Dark Matter - Ivanov, M. Ja.; Terentieva, L. V. (Physics of Entropy, Radiation and Gravitating Matter with Examples of General and Analytical Solutions, 2021)
The paper considers the two-fluid hydrodynamic model of Newtonian Dark Matter as a gaseous electrical and gravitational continues medium. The whole range of exact solutions for the Newtonian dark matter equations system is studied. Here many exact solutions have soliton-like structure similar to the known soliton solutions in the plasma physics. These solutions can be used for simulation of a few intrigue astrophysics phenomena. They can explain the gamma-ray bursts propagation and their afterglow. Other particle-like solutions simulate the ultra-high energy cosmic rays. These solutions explain propagation of the high energy cosmic rays to the very large cosmological distances without essential energy losses. As well the developed dark matter theory allows obtaining the exact solutions for the giant cosmic jets. The paper presents some results for the cosmic jets simulations and shows peculiarities of their propagation. Some results concern periodical waves in dark matter medium and particle-wave properties.